A conversion and pseudocapacitance-featuring cost-effective perovskite fluoride KCuF3 for advanced lithium-ion capacitors and lithium-dual-ion batteries. Issue 25 (16th June 2021) - Huang, Yuxi; Ding, Rui; Xu, Qilei; Shi, Wei; Ying, Danfeng; Huang, Yongfa; Yan, Tong; Tan, Caini; Sun, Xiujuan; Liu, Enhui
Abstract : A cost-effective perovskite fluoride KCuF3 material has been introduced as an advanced anode for lithium-ion capacitors (LICs) and lithium-dual-ion batteries (Li-DIBs), showing a conversion mechanism and pseudocapacitive kinetics for Li ion storage. Abstract : A cost-effective perovskite fluoride KCuF3 material has been introduced as an advanced anode for lithium-ion capacitors (LICs) and lithium-dual-ion batteries (Li-DIBs), showing a conversion mechanism and pseudocapacitive kinetics for Li ion storage.